Compreendendo o acolhimento em uma unidade de saúde da família na perspectiva dos usuários - Sato, Cintia Ayame [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The present study aimed at understanding humanized reception at a Family Health Unit in a city in São Paulo state according to users’ perspectives. It is a qualitative investigation with a Case Study as its methodological framework and the Theory of Complexity (TC) as its theoretical basis. Data were collected from March to July, 2011 by means of non-directive interviews and participant observation, and the Flowchart that analyzes the care provision model in health care services was used. The discourses were analyzed according to Bardin’s thematic approach, from which two themes emerged: humanized reception as an act that precedes medical consultation and humanized reception as a solution to demands stemming from medical action. The study provided visibility to the forms how humanized reception is understood, that is, the moment that precedes medical consultation, being configured as a pre-consultation instance when punctual actions are performed, such as measuring vital signs, and when users are sure that they will be seen by a doctor, in addition to the perception that humanized reception is not part of the process to solve their need, since such result is achieved by means of medication dispensation permeated by the polite treatment given by professionals. These results show how the fragmented, reductionist and linear approach to caregiving is still present in the words, thoughts and culture of health service users as well as in those of health care team members. TC seems to shed light on these issues, and it may result in important improvement in the understanding of interactional relationships between team members and users concerning the work process in the Family Health model as the main strategy in Primary Care

O presente estudo teve como objetivo compreender o acolhimento em uma Unidade de Saúde da Família de um município do interior paulista na perspectiva dos usuários. Trata-se de uma pesquisa qualitativa com o Estudo de Caso como referencial metodológico e a Teoria da Complexidade (TC) como referencial teórico. Os dados foram coletados nos meses de março a julho de 2011, por meio da entrevista não-diretiva e observação participante sendo utilizado o Fluxograma analisador do modelo de atenção de um serviço de saúde. Os discursos foram analisados na vertente temática de Bardin, de onde emergiram dois temas: O acolhimento como um ato que antecede a consulta médica e O acolhimento como solução de demandas decorrentes do ato médico. O estudo deu visibilidade às formas como são compreendidos o acolhimento, isto é, momento em que precede a consulta médica, sendo configurado como espaço de pré-consulta, onde se realiza ações pontuais como aferição de sinais vitais, e, que o usuário tem a certeza que será atendido pelo médico, além da percepção de que o acolhimento não faz parte do processo para resolução de sua demanda, pois, tal resultado se tem por meio da dispensação de medicamentos permeado por tratamento educado dos profissionais. Esses resultados demonstram como o olhar fragmentado, reducionista e linear do cuidado ainda estão presentes nas palavras, nos pensamentos, na cultura dos usuários dos serviços de saúde, bem como nos profissionais da equipe. A TC parece iluminar estas questões podendo resultar em importante melhoria da compreensão das relações interacionais entre equipe e usuários em torno do processo de trabalho no modelo Saúde da Família, enquanto principal estratégia da Atenção Básica
Keywords: Enfermagem – Estudo e ensino (Superior); Programa Saúde da Família (Brasil); Pesquisa qualitativa